Two new species of Monstera (Araceae: Monsteroideae) from Costa Rica - Cedeño-Fonseca, Marco; Croat, Thomas B.; Zuluaga, Alejandro; Mittermeier, Michael; Blanco, Mario A. (Phytotaxa, 2020)
Two species of Monstera, apparently endemic to Costa Rica, are newly described and illustrated. Monstera juliusii occurs in the southern Costa Rican portion of the Cordillera de Talamanca at 1600–2250 m, and has been confused with M. standleyana in herbaria. Monstera monteverdensis occurs in the Guanacaste and Tilarán cordilleras, and the northwestern part of the Cordillera Central, at 500–2300 m, and has been confused with M. epipremnoides, M. lentii and M. lechleriana in herbaria. Phenology and suggested conservation categories according to the IUCN Red List criteria are indicated for both new taxa.